In vitro maturation of immature oocytes from ovarian tissue prior to shipment to a cryobank - Dietrich, Jens Erik; Jauckus, Julia; Hoffmann, Sabrina; Liebenthron, Jana; Capp, Edison; Strowitzki, Thomas; Germeyer, Ariane (Archives of gynecology and obstetrics, 2020)
Female fertility preservation prior to gonadotoxic therapies can be achieved by the cryopreservation of ovarian cortical tissue. Immature oocytes may be recovered during the preparation, matured in vitro and lead to live births, thereby providing an additional option for fertility preservation. The purpose of this study was to test the feasibility of this approach in a setting with unilateral biopsy of a small piece of ovarian tissue and minimal tissue preparation prior to shipment to an external cryobank.
Gesehen am 08.09.2021